A heteromultivalent host-guest sensor array for cell recognition and discrimination - Hu, Xin-Yue; Hu, Zong-Ying; Tian, Jia-Hong; Shi, Lin; Ding, Fei; Li, Hua-Bin; Guo, Dong-Sheng (Chemical communications (Cambridge, England), 2022)
We present a supramolecular sensor array based on a series of heteromultivalent macrocyclic coassemblies using amphiphilic calixarenes and cyclodextrin as the building blocks for cell recognition. The corresponding cross-reactivity between the coassemblies and cells served as the unique fingerprint for cell classification, and successfully identified the normal cell lines, cancerous cell lines, and cross-contaminated cells. Supramolecular heteromultivalent sensor arrays were constructed by coassembling different amphiphilic calixarenes and cyclodextrin, and applied in cell identification.